Feasibility Study of Physician Orders for Life-Sustaining Treatment for Patients with Terminal Cancer - An, Ho Jung; Jeon, Hyun Jeong; Chun, Sang Hoon; Jung, Hyun Ae; Ahn, Hee Kyung; Lee, Kyung Hee; Kim, Min-ho; Kim, Ju Hee; Cheon, Jaekyung; Kim, JinShil; Koh, Su-Jin (Cancer research and treatment, 2019)
Physician Orders for Life-Sustaining Treatment (POLST) form is a legal document for terminally ill patients to make medical decisions with physicians near the end-of-life. A multicenter prospective study was conducted to evaluate the feasibility of POLST administration in actual oncological practice. Patients with terminal cancer, age ≥ 20 years, and capable of communicating were eligible. The primary endpoint was the completion rate of POLST. Data about physicians' or patients' barriers were also collected. From June to December 2017, 336 patients from seven hospitals were eligible. Median patient age was 66 years (range, 20 to 94 years); 52.7% were male; and 60.4% had poor performance status. Primary cancer sites were hepato-pancreato-biliary (26.2%), lung (23.2%), and gastrointestinal (19.9%). Expected survival duration was 10.6±7.3 weeks, with 41.2% receiving hospice care, 37.9% showing progression after cancer treatment, and the remaining patients were under active treatment (15.8%) or initially diagnosed with terminal cancer (5.1%). POLST forms were introduced to 60.1% of patients, and 31.3% signed the form. Physicians' barriers were reluctance of family (49.7%), lack of rapport (44.8%), patients' denial of prognosis (34.3%), lack of time (22.7%), guilty feelings (21.5%), and uncertainty about either prognosis (21.0%) or the right time to discuss POLST (16.6%). The patients' barriers were the lack of knowledge/understanding of POLST (65.1%), emotional discomfort (63.5%), difficulty in decision-making (66.7%), or denial of prognosis (14.3%). One-third of patients completed POLST forms, and various barriers were identified. To overcome such barriers, social engagement, education, and systematic support might be necessary.